Teach yourself visually iPad - Hart-Davis, Guy (Visual, a Wiley Brand, 2017)
Annotation
Date of publication from resource description page. - "Covers iOS 11 and iPad, iPad Pro, and iPad Mini"--Cover. - Online resource; title from cover (Safari, viewed April 16, 2018)
Keywords: iPad (Computer) -- Handbooks, manuals, etc; Tablet computers -- Handbooks, manuals, etc; Portable media players -- Handbooks, manuals, etc; iPad (Ordinateur); Guides, manuels, etc; Tablettes électroniques; Guides, manuels, etc; Baladeurs multimédias; Guides, manuels, etc; Tablet computers; Portable media players; iPad (Computer); handbooks; Handbooks and manuals; Guides et manuels; Handbook